Vacuum UV photo-oxidation of polystyrene. Issue 20 (17th October 2016) - Li, Xinyun; Toro, Marc; Lu, Fei; On, Jung; Bailey, Alla; Debies, Thomas; Mehan, Michael; Gupta, Surendra K.; Takacs, Gerald A.
Abstract: Polystyrene (PS) was treated with vacuum UV (VUV) ( λ = 104.8 and 106.7 nm) photo-oxidation and X-ray photoelectron spectroscopy detected a controlled increase in the atomic percentage of oxygen up to a saturation level of ca. 20 at% O. Initially, C–O and carbonyl groups are observed due to the formation of alcohols, ethers, esters, and ketones. Water contact angle measurements showed ca. 25% increase in hydrophilicity of the surface with oxidation. Atomic Force Microscopy observed little changes in surface roughness with treatment time. The super water absorbent polymer poly(acrylic acid) was thinly grafted to the modified PS surface.